A review: Virulence factors of Klebsiella pneumonia as emerging infection on the food chain - Riwu, Katty Hendriana Priscilia; Effendi, Mustofa Helmi; Rantam, Fedik Abdul; Khairullah, Aswin Rafif; Widodo, Agus (Veterinary World, 2022)
Health problems can be caused by consuming foods that have been processed in unsanitary conditions; hence, the study of the impact of contamination on food and its prevention has become critical. The disease caused by Klebsiella pneumoniae in food is increasing significantly every year across the world. The main factors that are essential for the virulence of K. pneumoniae are lipopolysaccharide and polysaccharide capsules. Furthermore, K. pneumoniae is capable of forming biofilms. Capsule polysaccharides, fimbriae types 1 and 3, are crucial virulence factors contributing to biofilm formation in K. pneumoniae. The food contamination by K. pneumoniae may not directly pose a public health risk; however, the presence of K. pneumoniae refers to unhygienic practices in food handling. This article aims to demonstrate that K. pneumoniae should be considered as a potential pathogen that spreads through the food chain and that necessary precautions should be taken in the future.